Misdemeanor Records and Employment Outcomes: An Experimental Study. (December 2019) - Leasure, Peter
This study examined whether misdemeanor drug convictions impact entry-level hiring outcomes. An experimental correspondence study was used whereby fictitious resumes are sent to employers. Resumes were randomly assigned to one of three conditions: no criminal record, 1-year-old misdemeanor record, and a 1-year-old felony record. Resumes were also randomly assigned with a distinctively White or African American name. Job type was used as an additional predictor. Results indicate that a misdemeanor conviction significantly hinders hiring outcomes for both African American and White applicants. However, results did not show statistically significant differences in the outcome between races. These results should be utilized to better inform defendants, practitioners, and policy-makers on the negative impacts of low-level convictions.